'Lighted' Assemblies of a PBI Derivative: Activation of Aerial Oxygen via Combined Charge and Energy Transfer Processes for Photocatalytic Oxidative Hydroxylation of Boronic Acids. Issue 10 (31st August 2021) - Singh, Gurpreet; Singh, Manpreet; Kumar, Sourav; Kumar, Manoj; Bhalla, Vandana
Abstract: The donor‐acceptor 'lighted' assemblies of PBI‐TPY have been developed, which exhibit strong absorption in the visible region, have high photostability, excellent electron transportation ability and high potential to activate aerial oxygen to generate reactive oxygen species, such as singlet oxygen, superoxide anion radical and hydroxide ions. Empowered by excellent photosensitizing properties, assemblies of PBI‐TPY exhibit high photocatalytic efficiency in visible light mediated oxidative hydroxylation of aromatic/aliphatic boronic acids through combined charge/energy transfer processes in the presence of weak electron donor (NEt3 ) and air as the 'oxidant' in mixed aqueous media. The work being presented in this manuscript also reveales the potential of PBI‐TPY assemblies for gram‐scale preparation of phenol and recyclability of upto six catalytic cycles in the oxidative hydroxylation reaction. Abstract : The donor‐acceptor 'lighted' assemblies of PBI‐TPY have been developed, which exhibit strong absorption in the visible region, have high photostability, excellent electron transportation ability and high potential to activate aerial oxygen to generate reactive oxygen species, such as singlet oxygen, superoxide anion radical and hydroxide ions.